Mechanical cardiopulmonary resuscitation for patients with cardiac arrest - Jiang, Lei (Second Affiliated Hospital of Zhejiang University School of Medicine, 2011)
BACKGROUND: Although modern cardiopulmonary resuscitation (CPR) substantially decreases the mortality induced by cardiac arrest, cardiac arrest still accounts for over 50% of deaths caused by cardiovascular diseases. In this article, we address the current use of mechanical devices during CPR, and also compare the CPR quality between manual and mechanical chest compression. METHODS: We compared the quality and survival rate between manual and mechanical CPR, and then reviewed the mechanical CPR in special circumstance, such as percutaneous coronary intervention, transportation, and other fields. RESULTS: Compared with manual compression, mechanical compression can often be done correctly, and thus can compromise survival; can provide high quality chest compressions in a moving ambulance; enhance the flow of blood back to the heart via a rhythmic constriction of the veins; allow ventilation and CPR to be performed simultaneously. CONCLUSION: Mechanical devices will be widely used in clinical practice so as to improve the quality of CPR in patients with cardiac arrest.